Isolation and characterization of p19INK4d, a p16-related inhibitor specific to CDK6 and CDK4. - Guan, K L (1996)
Cyclin-dependent kinases 4 and 6 are complexed with many small cellular proteins in vivo. We have isolated cDNA sequences, INK4d, encoding a 19-kDa protein that is associated with CDK6 in several hematopoietic cell lines. p19 shares equal similarity and a common ancestor with other identified inhibitors of the p16/INK4 family. p19 interacts with and inhibits the activity of both CDK4 and CDK6 and exhibits no detectable interaction with the other known CDKs. p19 protein is present in both cell nuclei and cytoplasm. The p19 gene has been mapped to chromosome 19p13.2, and the level of its mRNA expression varies widely between different tissues. In contrast to p21 and p27 whose interaction with CDK subunits is dependent on or stimulated by the cyclin subunit, the interaction of p19 and p18 with CDK6 is hindered by the cyclin protein. Binary cyclin D1-p18/p19 or cyclin D1-CDK6 complexes are highly stable and cannot be dissociated by excess amounts of cyclin D1 or p19/p18 proteins, suggesting that p16 inhibitors and D cyclins may interact with CDKs 4 and 6 in a competing or potentially mutually exclusive manner.